Predicting Clinical Outcomes in Glioblastoma: An Application of Topological and Functional Data Analysis - Crawford, Lorin; Monod, Anthea; Chen, Andrew X.; Mukherjee, Sayan; Rabadán, Raúl (Journal of the American Statistical Association, 2020)
Glioblastoma multiforme (GBM) is an aggressive form of human brain cancer that is under active study in the field of cancer biology. Its rapid progression and the relative time cost of obtaining mo...